2016
DOI: 10.1080/00036846.2016.1262516
|View full text |Cite
|
Sign up to set email alerts
|

The influence of CSR on firm value: an application of panel smooth transition regression on Taiwan

Abstract: Previous studies on the relationship between corporate social responsibility (CSR) and firm value generally belong to one of the two opposing schools of thought: the social impact hypothesis and the shift of focus hypothesis. This study, however, proposes that the relationship between CSR and company value is non-linear and neither wholly positive nor negative. We employed the corporate social responsibility index (CRSI) to test this hypothesis. The panel smooth transition regression (PSTR) model was used to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
42
2
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 64 publications
7
42
2
5
Order By: Relevance
“…The above table shows that, firstly, the corporate social responsibility disclosure index (CSRDI) had a positive and insignificant impact on the firm value (PBV). These results were consistent and support the research by [13], and [14]. This proves that the quality of CSR disclosure in the manufacturing industry sector of consumer goods industry listed on the BEI not fully follow the standards issued by GRI G3.…”
Section: Roa = (Net Profit After Tax) / (Total Assets) X 100%supporting
confidence: 91%
“…The above table shows that, firstly, the corporate social responsibility disclosure index (CSRDI) had a positive and insignificant impact on the firm value (PBV). These results were consistent and support the research by [13], and [14]. This proves that the quality of CSR disclosure in the manufacturing industry sector of consumer goods industry listed on the BEI not fully follow the standards issued by GRI G3.…”
Section: Roa = (Net Profit After Tax) / (Total Assets) X 100%supporting
confidence: 91%
“…CSR is a value creator for society and for the business, at least when it exceeds a given threshold (Chen and Lee, ). It needs to be understood along its determinants to ensure that its potential is fully gathered.…”
Section: Introductionmentioning
confidence: 99%
“…() further confirmed that integration of CSR into operational and management strategies, as well as corporate governance policies, increases the value of an enterprise. Similarly, Chen and Lee () indicated that when CSR activities over a certain threshold, operating expenses use to decrease and positively affect a firm's value.…”
Section: Introductionmentioning
confidence: 99%